Foreign Language Learning in Older Adults: Anatomical and Cognitive Markers of Vocabulary Learning Success - Fong, Manson Cheuk-Man; Ma, Matthew King-Hang; Chui, Jeremy Yin To; Law, Tammy Sheung Ting; Hui, Nga-Yan; Au, Alma; Wang, William Shiyuan (Frontiers in Human Neuroscience, 2022)
In recent years, foreign language learning (FLL) has been proposed as a possible cognitive intervention for older adults. However, the brain network and cognitive functions underlying FLL has remained largely unconfirmed in older adults. In particular, older and younger adults have markedly different cognitive profile—while older adults tend to exhibit decline in most cognitive domains, their semantic memory usually remains intact. As such, older adults may engage the semantic functions to a larger extent than the other cognitive functions traditionally considered the most important (e.g., working memory capacity and phonological awareness). Using anatomical measurements and a cognitive test battery, the present study examined this hypothesis in twenty cognitively normal older adults (58–69 years old), who participated in a two-month Italian learning programme. Results showed that the immediate learning success and long-term retention of Italian vocabularies were most consistently predicted by the anatomical measures of the left pars orbitalis and left caudal middle frontal cortex, which are implicated in semantic and episodic memory functions. Convergent evidence was also found based on the pattern of cognitive associations. Our results are consistent with a prominent role of semantic and episodic memory functions in vocabulary learning in older learners.